The ZEPLIN II dark matter detector: Data acquisition system and data reduction - Alner, G. J. (2008)
ZEPLIN II is a two-phase (liquid/gas) xenon dark matter detector searching for WIMP-nucleon interactions. In this paper we describe the data acquisition system used to record the data from ZEPLIN II and the reduction procedures which parameterise the data for subsequent analysis.